If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(6y * 4x) = 65 Reorder the terms for easier multiplication: 5x(6 * 4y * x) = 65 Multiply 6 * 4 5x(24y * x) = 65 Multiply y * x 5x(24xy) = 65 Remove parenthesis around (24xy) 5x * 24xy = 65 Reorder the terms for easier multiplication: 5 * 24x * xy = 65 Multiply 5 * 24 120x * xy = 65 Multiply x * xy 120x2y = 65 Solving 120x2y = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '120y'. x2 = 0.5416666667y-1 Simplifying x2 = 0.5416666667y-1 Combine like terms: 0.5416666667y-1 + -0.5416666667y-1 = 0.0000000000 x2 + -0.5416666667y-1 = 0.0000000000 Factor out the Greatest Common Factor (GCF), 'y-1'. y-1(x2y + -0.5416666667) = 0.0000000000Subproblem 1
Set the factor 'y-1' equal to zero and attempt to solve: Simplifying y-1 = 0 Solving y-1 = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y-1' to each side of the equation. y-1 + -1y-1 = 0 + -1y-1 Remove the zero: 0 = -1y-1 Simplifying 0 = -1y-1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(x2y + -0.5416666667)' equal to zero and attempt to solve: Simplifying x2y + -0.5416666667 = 0 Reorder the terms: -0.5416666667 + x2y = 0 Solving -0.5416666667 + x2y = 0 Move all terms containing x to the left, all other terms to the right. Add '0.5416666667' to each side of the equation. -0.5416666667 + 0.5416666667 + x2y = 0 + 0.5416666667 Combine like terms: -0.5416666667 + 0.5416666667 = 0.0000000000 0.0000000000 + x2y = 0 + 0.5416666667 x2y = 0 + 0.5416666667 Combine like terms: 0 + 0.5416666667 = 0.5416666667 x2y = 0.5416666667 Divide each side by 'y'. x2 = 0.5416666667y-1 Simplifying x2 = 0.5416666667y-1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (x)(2x)=28x | | 12+n=-17 | | -8-4(1+6f)=-33 | | 4x+1-(6)=3+2x | | 5(4)-10y=20 | | 2/-7/-4= | | 3x+7-2x-1=x+10 | | X-2+x-2=x+3 | | -2(4s-5)-10=-2(9s+8)-3 | | 5(3)-10y=20 | | 5x(x)+75+5=2x+52 | | (2x+2)(2x+2)=168 | | 17=3(a+3)-a | | 5(1)-10y=20 | | 28x^2-68x=48 | | 19(4c-1)-8=74c+19 | | 127+8d=19+20d | | 5(-1)-10y=20 | | 2b^2-14b=b-7 | | 0=9x^2+3x-2 | | x^3+-3x^2+-22x=-24 | | 2(3x+5)+22=-4(2x-15) | | 5(-2)-10y=20 | | (6y+7)-(6+5y)=9 | | Y=4-5(-1) | | 18(v+4)-2v=4(4v+1)-8 | | 2*20-3x= | | 4(-7k+5)=-2-6k | | -0.3x+9.86=-0.1x+6.86 | | 6+5m= | | x^2+4x=75 | | -8-4(4p+3)=30-6p |